(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Consumption calculation to measure the level of poverty in Indonesia was based on the average of expenditure per capita approach. The approach did not consider the age’s composition of household members. With such approach, the calculation of poverty level should not provide accurate figures and need to be evaluated. The equivalent scale approach to measure the level of poverty was used by considering the household member’s age composition. The result of poverty calculation using the equivalent scale approach gave the level of poverty at a more proportionate level compared to the average expenditure per capita approach. The main problem in applying the equivalent scale approach to calculate the level of poverty in Indonesia is the lack of equivalent scale formula suitable for Indonesian consumption household pattern.